Community perceptions of gender norms and economic opportunity in Solomon Islands - Nuia, Neil (Oxfam, 2019)
Presented by Neil Nuia (Oxfam), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.